Spontano predrtje žolčnika - Gajzer, Borut (Medicinski razgledi, 2000)
Gallbladder perforation can appear as an acute perforation followed by biliaryperitonitis, as subacute perforation with the formation of a pericholecystic abscess, or as a chronic condition leading to cholecysto-enteric fistula formation. It is mainly associated with gallbladderdiseases caused by gallstones, although gallstones are not necessarily an essential feature of perforation. Male sex, diabetes mellitus, atherosclerosis, immune system suppression, carcinoma, parentexal nutrition and severe hepatic diseases are involved as risk factors for , gallbladder perforation. Early suspicion and prompt surgical intervention are vital in thetreatment of patients with gallbladder perforation due to the high mortality rate of this condition. Ultrasonography of the abdomen is the most frequently used diagnostic tool, but cholescintigraphy is the most accurate one in demonstrating a perforated gallbladder. A preoperative diagnosis of a perforation is rare. This report concerns a younger patient with an acute spontaneous gallbladder perforation and diffuse biliary peritonitis. A diagnosis of a perforation was not made until during the operation. No gallstones or other risk factors for gallbladder perforation were found, but the pathohistological examination revealed cholesterolosis and a mild chronic inflammation of the gallbladder.
Keywords: Gallbladder diseases; žolčnik; predrtje; Rupture, spontaneous; vnetja; Cholelithiasis; Biliary fistula; Adult; diagnostika